1994
DOI: 10.1073/pnas.91.10.4204
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphorylation of Blk and Fyn Src homology 2 domain-binding proteins occurs in response to antigen-receptor ligation in B cells and constitutively in pre-B cells.

Abstract: Proteins that bind to discrete domains of the Blk, Fyn, Lyn, and Btk protein tyrosine kinases were emied in pre-B cells that had not been subjected to any external stimulation, as well as in nonstimulated and antigen-receptorligated B cells. Proteins that bind to the Src homology 2 domains of Blk and Fyn were identified in B cells that had been activated with anti-IgM but were not identified in unstimulated B cells. A number of Blk and Fyn Src homology 2 domainbinding phosphoproteins were also observed in pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…Receptor oligomerization induced after Ag binding is thought to be a required step for generating signals leading to responses such as negative selection and activation (17,39). However, it is becoming increasingly apparent that both the BCR and the pre-BCR on developing B cells are capable of generating signals independently of ligand (Ag) binding (24,31,32,35,51,52). Despite several reports that implicate ligand-independent BCR signaling in B cell development, neither it's regulation nor its linkage to specific events in B cell biology have been carefully studied.…”
Section: Discussionmentioning
confidence: 99%
“…Receptor oligomerization induced after Ag binding is thought to be a required step for generating signals leading to responses such as negative selection and activation (17,39). However, it is becoming increasingly apparent that both the BCR and the pre-BCR on developing B cells are capable of generating signals independently of ligand (Ag) binding (24,31,32,35,51,52). Despite several reports that implicate ligand-independent BCR signaling in B cell development, neither it's regulation nor its linkage to specific events in B cell biology have been carefully studied.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we have found that the cytoplasmic domains of Ig␣ and Ig␤ in the absence of extracellular or transmembrane domains are sufficient to trigger B cell development to transitional stages supporting a model where an unligated receptor is sufficient for this function. Accordingly, fluorescence resonance energy transfer studies support that the BCR is present in a monomeric form in resting B cells (22) and Src tyrosine kinases are found in close association with the unligated receptor (23)(24)(25).…”
mentioning
confidence: 89%
“…[7][8][9][10][11][12] In erythroid cells, Btk is associated with the Epo-receptor 8,13 whereas in (pre) B cells, Btk is coupled to the (pre) B-cell receptor (BCR). [10][11][12]14,15 In XLA patients, BTK mutations can be found throughout the gene and these frequently result in the absence of the Btk protein, 16,17 but amino acid replacements also occur. 18 XLA has a heterogeneous phenotype and this heterogeneity might be related to the nature of the mutation in combination with other genetic factors.…”
Section: Introductionmentioning
confidence: 99%